Challenges and Potentialities for Implementing Social Protection Responses to Emergency Through Decentralized Administration : Lessons from Brazil’s Auxilio Emergencial - Lara de Arruda, Pedro; Lazarotto de Andrade, Marina; Falcao, Tiago; Teixeira Barbosa, Diana; Morgandi, Matteo (World Bank, Brasilia, 2022)
With the advent of Coronavirus disease 2019 (COVID-19), Brazil has come out with one of the fastest and most generous social protection responses globally. Auxilio Emergencial (AE’s) operation is in contrast to that of regular social protection programs due to its highly centralized setup with limited formal involvement of subnational governments. Therefore, this analysis aims at understanding some core reasons why this happened and what were the main implications of this centralized operation to the program. The text also describes measures that were enacted to mitigate challenges due to the exclusion of subnational governments from the operation of AE and discusses the extent to which these can integrate traditional decentralization mechanisms of regular programs in the future and further improve the sectoral case management capacity at large. This paper is structured in seven chapters. Chapter one is introduction, chapter two presents a conceptual framework describing main forms of decentralization and discussing their adequacy to different contexts and traditional functions of the social protection sector. Chapter three presents an overview of AE highlighting its centralized setup and already discussing some main reasons why traditional decentralization mechanisms, such as the unified social assistance system (SUAS), were not formal members of the program. Chapter four discusses legacies of SUAS historical support to social protection in Brazil and how these have contributed to AE even if the system was not formally involved in the program. Chapter five describes some main challenges faced by AE and that can arguably have been mitigated had SUAS and or other subnational governments been part of its formal operation. Chapter six considers how SUAS and decentralized forms of social protection were nevertheless relevant as complementary measures to that provided by AE. Finally, chapter seven concludes by summarizing some core lessons learned for engaging decentralized mechanisms in emergency responses in the future.